Invasive fungal disease of the sinus and orbit: a comparison between mucormycosis and Aspergillus. Issue 2 (25th June 2015) - Trief, Danielle; Gray, Stacey T; Jakobiec, Frederick A; Durand, Marlene L; Fay, Aaron; Freitag, Suzanne K; Lee, N Grace; Lefebvre, Daniel R; Holbrook, Eric; Bleier, Benjamin; Sadow, Peter; Rashid, Alia; et al.
Abstract : Background/aims: Invasive fungal infections of the head and neck are rare life-threatening infections where prompt diagnosis and intervention is critical for survival. The aim of this study is to determine the clinical characteristics and outcomes of invasive fungal disease of the sinus and orbit, and to compare mucormycosis and Aspergillus infection. Methods: A retrospective review was conducted from a single tertiary care eye and ear hospital over 20 years (1994–2014). Twenty-four patients with a confirmed pathological diagnosis of invasive fungal disease of the sinus and/or orbit were identified and their medical records were reviewed. The main outcome measures were type of fungus, location of disease, mortality and visual outcome. Results: Patients with orbital involvement had a higher mortality and higher likelihood of mucormycosis infection compared with those with sinus-only disease (78.6% vs 20%, p=0.01; 86% vs 30%, p=0.01, respectively). Patients with mucormycosis had a higher mortality (71%) than patients with Aspergillus (29%); however, this was not statistically significant (p=0.16). All patients with orbital involvement and/or mucormycosis infections were immunosuppressed or had inadequately controlled diabetes, and had a cranial neuropathy or ocular motility dysfunction. All five post-transplant patients with orbital infections died, while the two transplant patients with sinus infections survived. Conclusions: Patients with orbital fungal infections are more likely to be infected with mucormycosis compared with Aspergillus and have a higher mortality compared with infections sparing the orbit. History of transplant portends a dismal prognosis in orbital infections. Invasive fungal disease should be considered in any immunocompromised patient presenting with a new cranial neuropathy or ocular motility abnormality.